Neutrophil activation during acute human anaphylaxis: analysis of MPO and sCD62L. Issue 3 (13th January 2017) - Francis, A.; Bosio, E.; Stone, S. F.; Fatovich, D. M.; Arendts, G.; Nagree, Y.; Macdonald, S. P. J.; Mitenko, H.; Rajee, M.; Burrows, S.; Brown, S. G. A.
Summary: Background: The mechanisms involved in the amplification of the mast cell response during anaphylaxis are unclear. Mouse models of anaphylaxis demonstrate the critical involvement of neutrophils. These innate immune cells are highly abundant in peripheral blood and can be rapidly activated to trigger both local and systemic inflammation. Objective: To investigate neutrophil activation in peripheral blood during acute human anaphylaxis. Methods: Patients presenting to the emergency department with anaphylaxis underwent blood sampling upon enrolment and at up to three subsequent time‐points. Traditional anaphylaxis biomarkers, histamine and mast cell tryptase, were measured by ELISA and ImmunoCAP, respectively. Plasma myeloperoxidase concentrations were measured by ELISA, serum soluble CD62L concentrations by cytometric bead array, and both compared to healthy controls. Results: In 72 patients, 37 (51%) had severe anaphylaxis, 33 (60%) were histamine positive, and 47 (70%) were mast cell tryptase positive. At enrolment, myeloperoxidase concentrations were 2.9‐ (95% CI: 1.3, 6.5) and 5.0‐ (95% CI: 2.4, 10.5) fold higher in moderate and severe patients, respectively, compared with healthy controls, and remained stable over the first 5 h following symptom onset. At enrolment, soluble CD62L was 29% (95% CI: 19, 38) and 31% (95% CI: 22, 40) lower in moderate and severe patients, respectively, than healthy controls, and was stable over the first 5 h. There were no associations between myeloperoxidase or soluble CD62L concentrations and either histamine or mast cell tryptase concentrations. Conclusions and Clinical Relevance: These results provide compelling evidence for the involvement of neutrophils during acute human anaphylaxis, suggesting they are activated early in the reaction, regardless of mast cell activation. This important finding increases our understanding of the basic mechanisms of anaphylaxis, a necessary precursor to improving treatment and prevention.